Alternative Policy in Managing Sustainable Genetic Resources of Local Beef Cattle for National Livestock Breeding System - Hardjosubroto, Wartomo (Indonesian Bulletin of Animal and Veterinary Sciences, 2004)
Various efforts have been done by the government to enhance the productivity and population of beef cattle in Indonesia. One of the programs that have been carried out for a long time is crossbreeding using artificial insemination method with frozen semen known as AI program. Not less than 10 breeds of imported beef cattle have been introduced . However, the cross breeding is not followed by a clear breeding program, thus if it is not straightened out it will have negative impacts on the quality of the breed. In fact, due to the decentralization euphoria several regions established their own Artificial Insemination station (AIS). Providing there is no clear breeding program carried out, there will be a decrease in the livestock productivity, such as the increase of inbreeding . Several alternatives in managing sustainable genetic resources of local beef cattle (for examples, Bali cattle, Madura cattle, Ongole cross breed, and Sumba Ongole) are: (1) The broadening of grass field through the integrated concept of plant and livestock and livestock "transmigration" ; (2) the alteration of regulations regarding the authority of the central government related to the quality of livestock genetic, the conservation of local cattle areas, and the authority of the National Germ plasm Commission; (3) Revitalization of the role of seed stock Institutes, reviving ranching ; and (4) The importance of cross breeding impacts on productivity and its economic contribution . Key words: Beefcattle, breeding system, alternative of policy